The Politics of Promotion: A Multimodal Analysis of the Ads of Punjab Government’s Welfare Schemes - Dr. Attiya Khanam; Dr. Sarwat Jabeen; Dr. Rashida Ahmad; Dr.Samia Manzoor (Al-Qanṭara, 2025)
This research conducts a multimodal discourse analysis of Chief Minister Punjab’s welfare schemes’ advertisements in Pakistan. The study mainly focuses on the intersection of politics, discourse, promotion and persuasion in these advertisements. It explores the elements of meaning making strategies that work by creating an interaction between the visual and verbal resources. These elements are analyzed under the multimodal frameworks of Machin (2007) and Machin & Mayr (2012) to understand the ideological combination of visual and verbal messages to persuade the audience. The study is qualitative in nature and purposive sampling has been used utilized. The findings reveal that the traditional symbols and references are used manipulatively and ideologically to reinforce the cultural and national identity of CM Punjab in these advertisements by creating an emotional cue while addressing social and economic issues of the public. These discourses build her persona as a strong and progressive leader by emphasizing on the benefits and success of these schemes. The discursive strategies are designed carefully to construct a narrative of development, progress and social welfare as well as promote CM Punjab as the heroic figure who is dedicated to improving the lives of people in all the advertisements.